Fostering a Saving Culture through Creative Activity-Based Financial Education among Elementary School Students - annisa izzahra; Mei Santi; Mohammad Riza Zainuddin (Sekolah Tinggi Agama Islam Darul Ulum Banyuanyar Pamekasan, 2026)
This community service activity aims to improve financial literacy and foster a culture of saving among elementary school students through an educational and creative approach. The target participants were students in grades 1–3 at SD Negeri 1 Kepuhrejo, Tulungagung. The activity employed a combination of financial education, direct practice, creative activities, educational games, and saving simulations. Student understanding was evaluated qualitatively through observation, question-and-answer sessions, and simple reflective evaluation conducted before and after the learning activities. The evaluation focused on students’ ability to explain the concept of money, distinguish between needs and wants, and demonstrate saving behavior during the simulation. The results showed a positive change in students’ understanding, as reflected in their ability to respond to questions and identify examples of needs and wants after the educational session. Students also demonstrated greater willingness to set aside pocket money during the saving simulation and expressed interest in continuing to use their decorated piggy banks. These findings indicate that combining financial education with creative and experiential activities can support the development of basic financial literacy and positive saving attitudes among elementary school students. The activity provides a practical model that can be adapted and replicated in other elementary school settings.